Throwing the bones to diagnose HIV: Views of rural South African traditional healers on undertaking HIV counselling and testing. Issue 10 (3rd October 2021) - Audet, Carolyn M.; Clemens, Elise M.; Ngobeni, Sizzy; Mkansi, Mevian; Sack, Daniel E.; Wagner, Ryan G.
ABSTRACT: In 2018, nearly 800, 000 HIV positive individuals in South Africa were unaware of their status. Traditional healers see patients who avoid health clinics, including those who refuse HIV testing. This manuscript details the results of a qualitative study to understand traditional healer perspectives on performing healer-initiated HIV counseling and testing HIV in rural South Africa. We conducted 30 structured in-depth interviews between April and June 2019 to elicit traditional healer attitudes towards partnering with local health services to perform HIV counseling and testing with their patients. Healers reported that while some patients are open about their HIV status, others lie about it due to stigma. This creates challenges with concurrent treatment, which healers believe leads to allopathic and/or traditional medication treatment failure. Most healers expressed both an interest and a willingness to perform HIV counseling and testing. Healers felt that by performing testing in the community, it would overcome issues related to HIV stigma, as well as a lack of confidentiality and trust with health care workers at the clinic. Trained traditional healers may be able to bridge the testing gap between "non-testers" and the allopathic health system, essentially "opening" thousands of new testing locations with little financial investment.